Influencia de pH y relación de mezcla de minerales óxidos/sulfuros, sobre la recuperación de oro y plata mediante flotación bulk - Ponce Quiñones, Hermes Lucio (2023)
The effects of hydrogen potential (pH) and oxide/sulfide mineral mixture ratio on the recovery of gold and silver by bulk flotation were investigated for using a mineral composite with the following chemical composition for the oxide-type mineral: 3.1 g/t Au, 110.5 g/t Ag, 0.03% Cu, 0.82% As, and for the sulfide-type mineral: 9.5 g/t Au, 57.89 g/t Ag, 36.76% Fe, 21.56% As. A bifactorial design was used, with the variable hydrogen potential (pH), which was evaluated at levels 5.0, 6.0 and 7.0, and the ratio of oxides/sulfides variable: (0/1), (3/1), (5/1), (7/1), (9/1), (1/0) with the dependent variable being the percentage recovery of gold and silver. A concentrate with an average gold recovery of 59.31%, gold grade 12.27 g/t, 62.80% silver recovery, and silver grade 226.08 g/t, and a concentration ratio of 3.61 was produced by mixing this type of oxide ore with sulfides at pH 6, with a mixing ratio of 3 parts oxides to 1 part sulfide. According to the analysis of variance results obtained for pH P=0.000, for oxide-sulfide mixture ratio P=0.000, and for the interaction of pH with oxide-sulfide mixture ratio P=0.000, it can be concluded that pH and oxide-sulfide mixture ratio influence the recovery of gold and silver by bulk flotation.